2012
DOI: 10.1021/es204519d
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Induced Degradation of Atrazine Sorbed in Mineral Micropores

Abstract: ABSTRACT:The herbicide atrazine is a common pollutant in reservoirs and other sources of drinking water worldwide. The adsorption of atrazine from water onto zeolites CBV-720 and 4A, mesoporous silica MCM-41, quartz sand, and diatomite, and its microwave-induced degradation when sorbed on these minerals, were studied. Dealuminated HY zeolite CBV-720 exhibited the highest atrazine sorption capacity among the mineral sorbents because of its high micropore volume, suitable pore sizes, and surface hydrophobicity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 54 publications
3
58
0
Order By: Relevance
“…Microporous structures in zeolite can provide a high surface area for chemical sorption and microbial attachment (Hu et al, 2012a), while bridging hydroxyls are catalytically active for various chemical reactions (Boscoboinik et al, 2013). This could explain the best performance of the zeolite CWs in removing the antibiotics and ARGs as well as conventional pollutants from raw wastewater.…”
Section: Discussionmentioning
confidence: 99%
“…Microporous structures in zeolite can provide a high surface area for chemical sorption and microbial attachment (Hu et al, 2012a), while bridging hydroxyls are catalytically active for various chemical reactions (Boscoboinik et al, 2013). This could explain the best performance of the zeolite CWs in removing the antibiotics and ARGs as well as conventional pollutants from raw wastewater.…”
Section: Discussionmentioning
confidence: 99%
“…The degradation of atrazine followed pseudo zero-order kinetics and atrazine could be fully mineralized under continuous microwave irradiation via a series of dechlorination-hydroxylation, Ndealkylation, dechlorination, dealkylation, and ring cleavage reactions. 15 The energy of microwave radiation (0.98 J/mol at 2.450 GHz) is very low and far less than the bond energies of common chemical bonds in organic molecules (for example, the dissociation energy for C−C bond is 348−356 kJ/mol). 16 Therefore, microwave radiation cannot be directly responsible for the degradation of atrazine sorbed in mineral micropores.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Instead, interfacial selective heating of microwave creates microscale "hot spots" near the pore wall surfaces, which causes degradation of the sorbed atrazine molecules via pyrolysis. 10,15 In our experimental study, the microporous minerals were irradiated with microwave after adsorption of atrazine from aqueous solution. Microwave energy penetrates the pore wall (with some or little dissipation depending on the dielectric properties of the minerals) and is transferred to the pore wall surfaces, and the atrazine and water molecules sorbed in the micropores by interaction of the electromagnetic field.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Our research has shown that microporous minerals can serve as excellent sorbents for organic contaminants and minerals with more hydrophobic pore spaces exhibit higher sorption capacities [13][14][15]. Dealuminated Y zeolites with high Si/Al ratios have been observed to exhibit high sorption capacities towards atrazine [16,17]. Consequently, microporous minerals are good candidates for sorbents used in packed columns, similar to activated carbon, for removing atrazine from aqueous stream.…”
Section: Atrazine [2-chloro-4-(ethylamino)-6-(isopropylamino)-striazine]mentioning
confidence: 76%